2022
DOI: 10.3390/biology11081171
|View full text |Cite
|
Sign up to set email alerts
|

Micrococcus lylae MW407006 Pigment: Production, Optimization, Nano-Pigment Synthesis, and Biological Activities

Abstract: Bacterial pigments (e.g., melanin and carotenoids) are considered to be among the most important secondary metabolites due to their various pharmacological activities against cancer and microbial resistance. Different pigmented bacterial strains were isolated from soil samples from El Mahmoudiyah governance and screened for their antimicrobial activity. The most promising pigment producer was identified as Micrococcus lylae MW407006; furthermore, the produced pigment was identified as echinenone (β-carotene pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
(42 reference statements)
2
10
0
Order By: Relevance
“…Glucose was better for pigment synthesis, fructose was better for fungal growth, while, lower pigment production and biomass were obtained with β-cyclodextrin and starch. In accordance with our results, Zhao et al (2019) and Shahin et al (2022) stated that glucose was the optimum carbon source for pigment production.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Glucose was better for pigment synthesis, fructose was better for fungal growth, while, lower pigment production and biomass were obtained with β-cyclodextrin and starch. In accordance with our results, Zhao et al (2019) and Shahin et al (2022) stated that glucose was the optimum carbon source for pigment production.…”
Section: Resultssupporting
confidence: 92%
“…Glucose was better for pigment synthesis, fructose was better for fungal growth, while, lower pigment production and biomass were obtained with β-cyclodextrin and starch. In accordance with our results, Zhao et al (2019) and Shahin et al (2022) stated that glucose was the optimum carbon source for pigment production. Nitrogen source, another essential building component, can influence microbial growth and the production of bioactive metabolites (Tudzynski, 2014;Landi et al, 2019;Darwesh et al, 2020).…”
Section: Optimization Of Pigment Production By Strain Sybc-l7supporting
confidence: 93%
“…and Virgibacillus sp. were previously reported [ 16 , 26 , 27 ]. The ability of carotenoids to inhibit bacteria may be due to their ability to interact with proteins located in the outer membranes of bacterial cells, causing membrane damage that restricts the availability of nutrients needed for bacterial growth and, ultimately, results in bacterial death [ 28 , 29 ].…”
Section: Resultsmentioning
confidence: 87%
“…The optimum growth and pigment production by C. parietis AUCs were achieved in nutrient broth at pH 8, 35 °C after 72 h under 150 rpm. Many researchers have reported that the production of bacterial pigments is influenced by culture and environmental conditions [ 10 , 16 , 17 ].
Fig.6 Optimization of pigment production by C. parietis AUCs
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation